KARAKTERISASI TEPUNG UBI KAYU MODIFIKASI YANG DIPROSES MENGGUNAKAN METODE PRAGELATINISASI PARSIAL - Beni Hidayat; Nurbani Kalsum; Surfiana Surfiana (Jurnal Teknologi & Industri Hasil Pertanian, 2009)
This research was aimed to characterize modified cassava flour processed through partial pregelatinisation method  compared to sawut cassava flour as a control.  The results showed the application of partial pregelatinization method produced cassava flour that has different characters compared to sawut cassava flour. The characters were different in the term of color reaction complex with iodine (redish purple compared to blue),  the microscopic apearance of starch granules (swelling condition compared to not swelling/native condition), gelatinization temperature (87.0oC compared to 75.0oC), maximum viscosity (965 BU compared to 900 BU), whiteness degree (86.20% compared to 78.76%), water absorption (2.36 g/g compared to 0.13 g/g), water solubility (0.25 g/ml compared to 0.13 g/ml), amylose content (32.67% compared to 15.32%), and odour (3.85 compared to 2.37). Key words : Modified cassava flour, pregelatinisation method, sawut